Aspiration Incidentally Detected by a Meckel Scintigraphy. (December 2017) - Bai, Xia; Fostitsch, Johannes C.; Zhuang, Hongming
Abstract : Abstract: Meckel scintigraphy with 99m Tc-pertechnetate was performed in a 5-year-old boy to determine whether a Meckel diverticulum containing ectopic gastric mucosa caused bleeding. The images did not reveal focal activity characteristic of a Meckel diverticulum. Unexpectedly, activity in the tracheobronchial tree was visualized, consistent with aspiration of the radioactive saliva.